Supernatural belief is not modulated by intuitive thinking style or cognitive inhibition - Farias, Miguel; van Mulukom, Valerie; Kahane, Guy; Kreplin, Ute; Joyce, Anna; Soares, Pedro; Oviedo, Lluis; Hernu, Mathilde; Rokita, Karolina; Savulescu, Julian; Möttönen, Riikka (Nature Publishing Group, 2017)
According to the Intuitive Belief Hypothesis, supernatural belief relies heavily on intuitive thinking—and decreases when analytic thinking is engaged. After pointing out various limitations in prior attempts to support this Intuitive Belief Hypothesis, we test it across three new studies using a variety of paradigms, ranging from a pilgrimage field study to a neurostimulation experiment. In all three studies, we found no relationship between intuitive or analytical thinking and supernatural belief. We conclude that it is premature to explain belief in gods as ‘intuitive’, and that other factors, such as socio-cultural upbringing, are likely to play a greater role in the emergence and maintenance of supernatural belief than cognitive style.